Green and climate finance research trends: A bibliometric study of pre- and post-pandemic shifts - Azhar Mohamad (Cleaner Production Letters)
Green and climate finance are critical for solving global climate concerns and promoting sustainable development. However, research gaps remain in identifying theme shifts and regional discrepancies, particularly in the aftermath of the COVID-19 pandemic. This study undertakes a bibliometric analysis of 1039 Scopus papers published between 1997 and 2024, utilising tools including Bibliomagika, VOSviewer, and Biblioshiny to look at co-authorship networks, keyword co-occurrence, and thematic clusters. The findings emphasise a significant increase in research output following 2020, which indicates the increasing significance of sustainable financial mechanisms. China is becoming a global centre for research collaboration, while journals such as Environmental Science and Pollution Research are the most prolific in terms of publications and citations. Thematic analysis indicates a transition from adaptation and food security prior to the pandemic to green finance, renewable energy, and sustainable development goals during the pandemic. Nevertheless, climate finance has a substantial research gap, particularly in adaptation strategies. The study emphasises the necessity of strategic investments in green financial mechanisms and the integration of green finance into economic recovery frameworks, providing policymakers with actionable insights. The key to leveraging green and climate finance to achieve a sustainable, resilient future is to enhance interdisciplinary research and foster equitable global collaboration.